A Quick Glance at Paediatrics - Tagbo, Beckie Nnnenna (Cambridge Scholars Publishing, 2019)
This book represents a much-needed paediatric reference book, especially with regards to developing countries. It will be of interest and use to all professional stakeholders in paediatrics and child health, including paediatricians, general practitioners, family medicine specialists, paediatric teachers and lecturers, and medical students. It covers a wide range of topics including clinical paediatrics, preventive and social paediatrics, infectious diseases, non-communicable diseases, child health, clinical history taking, systemic physical examination and clinical reasoning. It also consider.